Observation of Carbodicarbene Ligand Redox Noninnocence in Highly Oxidized Iron Complexes. (2nd November 2018) - Chan, Siu‐Chung; Gupta, Puneet; Engelmann, Xenia; Ang, Zhi Zhong; Ganguly, Rakesh; Bill, Eckhard; Ray, Kallol; Ye, Shengfa; England, Jason
Abstract: To probe the possibility that carbodicarbenes (CDCs) are redox active ligands, all four members of the redox series [Fe(1 )2 ] n + ( n =2–5) were synthesized, where1 is a neutral tridentate CDC. Through a combination of spectroscopy and DFT calculations, the electronic structure of the pentacation is shown to be [Fe III (1 .+ )2 ] 5+ ( S = 1 / 2 ). That of [Fe(1 )2 ] 4+ is more ambiguous, but it has significant contributions from the open‐shell singlet [Fe III (1 )(1 .+ )] 4+ ( S =0). The observed spin states derive from antiferromagnetic coupling of their constituent low‐spin iron(III) centres and cation radical ligands. This marks the first time redox activity has been observed for carbones and expands the diverse chemical behaviour known for these ligands.